Impaired Cerebral Autoregulation in Parkinson's Disease: An Orthostatic Hypotension Analysis - Xing, Yingqi; Li, Qing; Xu, Erhe; Zeng, Jingrong; Li, Qiuping; Mei, Shanshan; Hua, Yang (Frontiers in Neurology, 2022)
Orthostatic hypotension (OH) is an early manifestation of the non-motor features of Parkinson’s disease (PD). The underlying mechanism of hemodynamic changes in patients with PD and OH remains unclear. This study aimed to investigate the dynamic cerebral autoregulation changes in the PD population with OH. Ninety patients with PD and 20 age- and sex-matched healthy controls (HCs) were recruited. Non-invasive blood pressure and cerebral blood flow velocity were recorded simultaneously in the active standing test (AST) including the supine and orthostatic positions. Transfer function analysis was used to calculate autoregulatory parameters including gain and phase difference. OH was diagnosed in sixteen patients (17.8%) in the PD population (PD-OH). AST results were normal in seventy-four patients (82.2%) (PD-NOR). In the supine position, the PD-OH group had a lower phase degree than that of the PD-NOR group (50.3 ± 23.4 vs 72.6 ± 32.2 vs 68.9 ± 12.1, p=0.020); however, no significant difference was found when compared to the HC group. In the orthostatic position, the normalized gain was significantly higher in the symptomatic OH group than in the asymptomatic OH group and HC group (1.50 ± 0.58 vs 0.97 ± 0.29 vs 1.10 ± 0.31, p=0.019). Cerebral autoregulation has a tendency of impairment in the supine position in patients with PD and OH. Symptomatic OH in patients with PD implies that cerebral autoregulation is compromised in the orthostatic position.